1997
DOI: 10.1063/1.119913
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous electronic and magnetic transitions in La1−xKxMnO3 thin films

Abstract: We have fabricated perovskite La1−xKxMnO3 (x=0.14 and 0.2) thin films on SrTiO3 (100) by e-beam/thermal coevaporation. From the electrical and magnetic studies, we found a simultaneous occurrence of the paramagnetic to ferromagnetic state and insulating to metallic state, as predicted by the double exchange theory. The magnetoresistance is relatively small compared to that of the divalent cation doped La1−xAxMnO3 in fields up to 5 T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…It is possible to achieve an equal amount of hole doping with half the number of the monovalent ions, because for the same amount of aliovalent dopant the hole density is twice that of the divalent ion doping. Monovalent ion-doped rare earth manganites of the general formula, Ln 1-x A x MnO 3 (Ln = La, Pr, Nd; A = Na, K, Rb), provide another series of oxides to study the physical phenomena of insulator-to-metal transition and colossal magnetoresistance (Itoh et al 1995;Shimura et al 1996;Chen and de Lozanne 1997;Ng-Lee et al 1997;Sahana et al 1997;Singh et al 1998). Alkali metal ion doped lanthanum manganites have been prepared by the conventional ceramic methods (Itoh et al 1995;Shimura et al 1996), alkali-flux method (Singh et al 1998;Shivakumara et al 2004) and fused salt electrolysis (McCarroll et al 1999).…”
Section: +mentioning
confidence: 99%
“…It is possible to achieve an equal amount of hole doping with half the number of the monovalent ions, because for the same amount of aliovalent dopant the hole density is twice that of the divalent ion doping. Monovalent ion-doped rare earth manganites of the general formula, Ln 1-x A x MnO 3 (Ln = La, Pr, Nd; A = Na, K, Rb), provide another series of oxides to study the physical phenomena of insulator-to-metal transition and colossal magnetoresistance (Itoh et al 1995;Shimura et al 1996;Chen and de Lozanne 1997;Ng-Lee et al 1997;Sahana et al 1997;Singh et al 1998). Alkali metal ion doped lanthanum manganites have been prepared by the conventional ceramic methods (Itoh et al 1995;Shimura et al 1996), alkali-flux method (Singh et al 1998;Shivakumara et al 2004) and fused salt electrolysis (McCarroll et al 1999).…”
Section: +mentioning
confidence: 99%
“…11 Our previous studies on La 1Ϫx Ca x MnO 3 and La 1Ϫx K x MnO 3 using the same technique were reported elsewhere. 12,13 In brief, we used two electron beam sources to evaporate La and Mn. The relative atomic ratio between La and Mn was precalculated and converted into thickness as shown on the quartz crystal thickness monitors.…”
mentioning
confidence: 99%
“…The sample exhibited a special transport behavior [7,8], it shows that there were double peaks or shoulder in the temperature dependence of resistivity measurement. This phenomenon was initially explained by a possible phase inhomogeneity in La 1Àx A x MnO 3 (A=K, Na) sample due to their sintering in short time [9,10]. However, the second resistivity peak could not be removed no matter what synthesis techniques was used, either by preparing the bulk sample in a long sintering time or making thin film [9][10][11].…”
Section: Introductionmentioning
confidence: 97%
“…This phenomenon was initially explained by a possible phase inhomogeneity in La 1Àx A x MnO 3 (A=K, Na) sample due to their sintering in short time [9,10]. However, the second resistivity peak could not be removed no matter what synthesis techniques was used, either by preparing the bulk sample in a long sintering time or making thin film [9][10][11]. In this paper, we firstly investigate the effect of Nd doping in La 0.83Àx Nd x K y MnO 3 on the structure, the magnetic and transport properties in (La, K) MnO 3 , and try to find out the correlation among the structure, magnetic property and electronic transport property.…”
Section: Introductionmentioning
confidence: 99%